INSIGHT OF AYURVEDA IN DIABETIC RETINOPATHY: A REVIEW STUDY (International Journal of Ayurveda and Pharma Research, 2018)
Present day lifestyle i.e. change in eating habits, progressive weight gain, stress, pollution, tobacco use and a sedentary life style lead to increase in number of lifestyle disorders. One of such lifestyle related disorders is Diabetes Mellitus, which if not controlled later on leads to Neuropathy, Nephropathy, Cardiomyopathy and Retinopathy. Diabetic Retinopathy (DR) is considered as a most threatening complication of Diabetes Mellitus. Diabetics have a 20-25 times greater risk of blindness as compared to the normal population. In Ayurveda, Diabetes Mellitus can be coined with Madhumeha, as DR is due to its complication so it can be correlated with Madhumeha janya netra vikaar. Various Kriyakalpa procedures like Anjana, Aschyotan, Tarpan, Putpaka, other daily regimes like Snana, Padabhyanga, Abhyanga etc., are considered as highly effective procedures for the maintenance of eye health in DR. These measures help to modify lifestyle, promote psychosomatic health and thereby reducing psychosocial stress and help in prevention and management of a wide range of lifestyle disorders. The purpose of this presentation is to analyse Ayurveda’s preventive and therapeutic measures for treating DR and to evaluate how these measures can contribute towards improving the level of health care.